THE EFFECT OF COMPETENCY, INTRINSIC MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT NATIONAL UNIVERSITY MEDIATED BY KEY PERFORMANCE INDICATOR (KPI) ASSESSMENT - Dini Febriani; Suryono Efendi; Edi Sugiono (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the influence of competence, intrinsic motivation, and organizational culture on Key Performance Indicators (KPI) assessment and its implications for employee performance at Universitas Nasional. The results indicate that competence, intrinsic motivation, and organizational culture each have a positive and significant effect on KPI assessment. Furthermore, these three variables also positively and significantly affect employee performance. KPI assessment serves as an intervening variable that strengthens the relationship between competence, intrinsic motivation, and organizational culture with employee performance. The findings suggest that enhancing employees’ skills and knowledge, fostering intrinsic motivation, and implementing a positive organizational culture can improve KPI achievement, which in turn directly impacts employee performance. Therefore, human resource management focused on developing competence, strengthening intrinsic motivation, and creating a supportive organizational culture becomes a strategic factor in sustainably improving employee performance.